PEMODELAN INDIKATOR TUJUAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Retno Setianingtias; M. Baiquni; Andri Kurniawan (Jurnal Ekonomi dan Pembangunan, 2025)
A new direction in the current development process is the implementation of Sustainable Development Goals (SDGs). The concept of sustainable development is composed of four dimensions, namely economic, social, environmental and institutional development. TPB comes with 17 objectives and a number of indicators for measurement. This study aims to analyze the relationship between indicators and dimensions in sustainable development. The identification of indicators comes from the publication of Bappenas and BPS, as well as the results of previous studies. Data sourced from secondary data related agencies. The unit of analysis in this study is all provinces in Indonesia using 2015 data. The method used is Structural Equation Modeling using Partial Least Square to reduce indicators and see the relationship between social, economic, environmental and institutional dimensions. The indicator selection results show that of the fifty indicators, there are nineteen indicators that affect sustainable development. Modeling with SEM PLS provides an overview that between the dimensions of the economy - environment, economic - social, institutional - economic, economic - institutional, institutional - social, likeness - TPB, Environment - TPB, social - environment, social - TPB and TPB - the quality of development shows significant results, however there is an insignificant relationship, namely the relationship between the institution and the environment.